A Study of LQ 45 Index Companies Listed on The Indonesia Stock Exchange from 2019-2023 Examines The Impact of Environmental Accounting Disclosure and Performance on Company Value - Indika Rahmatul Saniah; Tatik Zulaika; Rini Oktavia (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2025)
The purpose of this study is to examine how environmental accounting disclosure and environmental performance affect the business value of the LQ-45 index listed on the IDX in 2019-2023. The methodology of this research is quantitative. The companies that are part of LQ-45 for the period 2019-2023 make up the research population. Purposive sampling was used to select samples, resulting in 14 observational samples. The IBM SPSS statistical 25 program is used to process the data. Multiple linear regression analysis is used as a data analysis method. With a significance value of 0.001 (<0.05), the research findings show that environmental accounting disclosure has a positive effect on company value. With a significance score of 0.009 (<0.05), environmental performance has a positive effect on the company's value